A study on tourism challenges at Tasik Kenyir / Taufiq A Rahman - A Rahman, Taufiq (Faculty of Business and Management, 2008)
Tourism is the act of travel for predominantly recreational or leisure purposes, and refers to the provision of services in support of this act. Tasik Kenyir is located in the interior of the Terengganu and spanning over 209, 199 hectares. It is the largest man-made lake in south east Asia. Sharing its border with Kelantan in the west and Pahang in the south , this immense lake also serve as another gateway to Taman Negara.